Use of Alzheimer family support group by community-residing caregivers - LaMore, Katherine Wood (Groupwork, 2012)
This paper describes the author’s experience as a new co-facilitator for an Alzheimer’s Disease Family Support Group and reviews the preliminary phase of group practice and the dynamics of the beginning phase of co-facilitating the Alzheimer’s Family Support Group. The paper reviews the needs that Alzheimer Support Group would meet, purpose of the group, agency and sponsorship support for Alzheimer Support Group, recruitment, group composition, group timing and structure, leadership of group, orientation of group members, content of group meetings, group sessions, and anticipated obstacles, and concludes with the importance of empowerment-oriented social workers who share the message that change is possible with others who are struggling, while working side-by-side with them to achieve changes and provide a new beginning – a new path for caregivers – a path of self discovery. As Alzheimer’s disease progresses caregivers and loved ones of people with the disease are often challenged on a daily basis – emotionally, mentally, and physically. Being with other people in similar situations encourages group members to share information, exchange coping skills, give and receive mutual support, vent their frustrations and share their success stories. Caregiving for a person with cognitive impairments can be a very difficult task, but knowing that you are ‘all in the same boat’ provides the life preserver to the caregiver – giving nourishment to the soul.